2022
DOI: 10.21203/rs.3.rs-1065379/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coronavirus (SARS-CoV-2) in Antillean Manatees (Trichechus Manatusmanatus)

Abstract: For two years, the world has been experiencing a coronavirus (SARS-CoV-2) pandemic. Non-human animals are susceptible to the virus, including marine mammals. Here we aimed to test Antillean manatees, Trichechus manatus manatus, for the coronavirus (SARS-CoV-2). We collected samples from 19 individuals kept under the responsibility of the Brazilian centre for research and conservation of aquatic mammals (ICMBio/CMA). We analysed the samples through RT-PCR and RT-LAMP-PCR and found that two of the 19 manatees te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Two Antilles manatees ( Trichechus manatus manatus ) were infected with SARS‐CoV‐2 at the National Center for Research and Conservation of Aquatic Mammals in Brazil. However, the animals did not exhibit clinical signs 6,24 . This is the first time that a marine mammal has been infected with SARS‐CoV‐2, and the case of infection in this species has only been reported in Brazil.…”
Section: Natural Infections In Animalsmentioning
confidence: 82%
See 2 more Smart Citations
“…Two Antilles manatees ( Trichechus manatus manatus ) were infected with SARS‐CoV‐2 at the National Center for Research and Conservation of Aquatic Mammals in Brazil. However, the animals did not exhibit clinical signs 6,24 . This is the first time that a marine mammal has been infected with SARS‐CoV‐2, and the case of infection in this species has only been reported in Brazil.…”
Section: Natural Infections In Animalsmentioning
confidence: 82%
“…The source of infection in the Antilles manatee is not yet clear, but it may have been infected by SARS‐CoV‐2‐positive staff, by contact with contaminated fomites in the environment. 24 …”
Section: Natural Infections In Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has a probable zoonotic origin [1,2]. SARS-CoV-2 infections have been detected in a variety of non-human animals, including domesticated cats [3], white-tailed deer [4], captive tigers [5], certain monkey species [6], Antillean manatees [7] and captive hippopotami [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, in mammals (non-humans), studies have focused on the susceptibility of different species to viral infection and their roles in the dissemination of COVID-19 ( Shi et al, 2020 , Tiwari et al, 2020 , Rockx et al, 2020 , Audino et al, 2021 , Mathavarajah et al, 2021a , Mathavarajah et al, 2021b , Gryseels et al, 2021 , Delahay et al, 2021 , Patel et al, 2021 , Melo et al, 2022 ). Although Rhea et al (2021) ) have recently demonstrated that intravenously injected radioiodinated S1 (I-S1) (S1 subunit of Spike protein of SARS-CoV-2) readily crossed the blood-brain barrier in male mice, was taken up by brain regions, and entered the parenchymal brain space, the consequences of this translocation have not been evaluated and therefore remain unknown.…”
Section: Introductionmentioning
confidence: 99%